Analisis Terhadap Kualitas Air Sungai Kaligarang sebagai Sumber Air Baku PDAM - Natasha Cindy Kardia Etnovanese; Tiyas Matilda Aprillia; Djoko Suwarno; Budi Setiyadi (Universitas Katolik Soegijapranata Semarang, 2019)
The usage of water should be wisely. Water which most used by the community is river water. Kaligarang river water is used for irrigation, to wash the clothes, cleanse sewage. and as the basic source of PDAM Tirta Moedal Semarang. This observation method is literature study, collect data by interview and take the water sample, and analysis the water quality. The observation of water quality is done to search for the cause of Kaligarang river pollution so that we know how to neutralize the river basic source in PDAM Tirta Moedal Semarang. The observation is done in the draught season because at this time the content of pollution is higher. The water sample is taken from the river junction, back of PDAM TM intake, and at the estuary. The quality criteria of water is based on PPRI number 82, 2001. The result shows that water at every spot has parameter which higher. Has high value parameter which is more than the limitation value which is different and the pollutant is much in the muara. The penetrate used by PDAM Tirta Moedal is chlorin and tawas, and the usage doesn not influent the cost of production nor distribution but it causes the production process stop, so that the people should have water containers at their homes.